Practice Through Play Using Mobile Technology - Garciano, Agnes D. (Archīum Ateneo, 2023)
This paper discusses the Just Keep Solving apps that are designed based on deliberate practice model for developing mathematical skills. Features of deliberate practice include well-defined goals involving areas of weakness as determined by a knowledgeable other such as a teacher. The integration of game design features provides a positive environment wherein the learning goals critical in a deliberate practice model are emphasized. Possible strategies for integrating the apps in a classroom are also discussed using Hughes, Thomas and Scharber’s RAT (Replacement, Amplification, Transformation) framework. The games can replace traditional pen-and-paper classroom activities, amplify learning by personalizing a student’s experience and providing opportunities for deliberate practice, and transform instruction from being teacher-centered to student-centered.